1993
DOI: 10.1037/h0095596
|View full text |Cite
|
Sign up to set email alerts
|

Transitional employment program for persons with long-term mental illness: A review.

Abstract: Persons labeled as having long-term mental illness are individuals with a diagnosis o f a psychological disorder o f prolonged duration with resulting functional or role incapacity. Historically mental health and vocational rehabilitation programs have not been successful in placing the long-term mentally ill in employment. Supported employment is a model that has been successful for the developmentally disabled and is used now for persons with long-term mental illness. The transitional employment program is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
5
0
4
Order By: Relevance
“…Transitional employment is offered to people with severe mental illness as a possible and significant step for members registered in Clubhouses -it is considered to be the ''lifeblood of clubhouse'' Phillips & Biller, 1993;Waters, 1992). Although Marrone (1993) noted that certain Clubhouses did not include transitional employment in their services; a study by Macias, Jackson, Schroeder, and Wang (1999) found that 82% of Clubhouses (N ¼ 173) included transitional employment programs.…”
Section: Transitional Programsmentioning
confidence: 97%
“…Transitional employment is offered to people with severe mental illness as a possible and significant step for members registered in Clubhouses -it is considered to be the ''lifeblood of clubhouse'' Phillips & Biller, 1993;Waters, 1992). Although Marrone (1993) noted that certain Clubhouses did not include transitional employment in their services; a study by Macias, Jackson, Schroeder, and Wang (1999) found that 82% of Clubhouses (N ¼ 173) included transitional employment programs.…”
Section: Transitional Programsmentioning
confidence: 97%
“…Ces services peuvent mettre l'accent sur la formation et la prépara-tion à l'emploi, sur les habiletés de recherche d'emploi, ou sur le placement, la formation et le suivi en milieu de travail (voir Barker, 1994 ;Cochrane et al, 1991 ;McGurrin, 1994 ;Phillips et Biller, 1993). L'efficacité de ces services demeure toutefois difficile à établir, les taux de succès rapportés dans la documentation scientifique variant non seulement entre types de services mais aussi entre services de même type.…”
Section: L'efficacité Des Services Offertsunclassified
“…www.erudit.org Tous droits réservés © Santé mentale au Québec, 1996 Santé mentale au Québec, 1996, XXI, 2, 73- L 'intégration socioprofessionnelle constitue un objectif important des programmes de réadaptation offerts aux personnes présentant des troubles mentaux. Outre les bénéfices économiques qui peuvent en dé-couler, l'exercice d'un travail peut avoir des retombées positives au plan psychologique et social (Connors et al, 1987;Frey, 1994;Frey et Godfrey, 1991 ;Phillips et Biller, 1993 ;Vincelette, 1995). Le travail serait, en outre, moins défavorable pour la santé mentale des personnes présentant des troubles que l'absence de travail (Vogel et al, 1989 ;Vostanis, 1990 Santé mentale au Québec L'intégration (ou la réintégration) socioprofessionnelle s'avère toutefois difficile pour ces personnes.…”
unclassified
See 1 more Smart Citation
“…L es pro blè mes de santé men tale coûtent 5,12 milliards par année au Qué bec en frais de santé et en perte de pro duc tion (Lau zon et al, 2000). L'exer cice d'un tra vail repré sente non seu le ment des gains éco nomi ques sub stan tiels, mais éga le ment un point d'an crage essen tiel pour la réadap ta tion des per son nes aux pri ses avec ces trou bles mentaux graves (Jacobs, 1991 ;Phillips et Biller, 1993 ;Scheid et Ander son, 1995). Selon Vos ta nis (1990), dans la réadap ta tion, le tra vail ne devrait pas être con sidéré comme un fac teur indé pen dant, mais comme un élé ment du pro cessus.…”
unclassified